Sensitive period for the plasticity of alpha activity in humans. (June 2021) - Campus, Claudio; Signorini, Sabrina; Vitali, Helene; De Giorgis, Valentina; Papalia, Grazia; Morelli, Federica; Gori, Monica
Highlights: Blind infants/children have alpha activity even if weaker vs sighted counterpart. First great differentiation within 3–6 Y. Lower alpha increases in blind the probability of motor impairment/hypotonia. Vision mediates the neural mechanisms generating alpha during earliest life. 3–6 Y is a sensitive period for the plasticity of this process in humans. Abstract: Visual experience is crucial for the development of neural processing. For example, alpha activity development is a vision-dependent mechanism. Indeed, studies report no alpha activity is present in blind adults. Nevertheless, studies have not investigated the developmental trajectory of this activity in infants and children with blindness. Here, we hypothesize that the difference in neural activity of blind compared to sighted subjects is: absent at birth, progressive with age, specifically occipital and linked to a gradual motor impairment. Therefore, we consider spectral power of resting-state EEG and its association with motor impairment indices, in blind subjects and in sighted controls between 0 and 11 years of age. Blind subjects show posterior alpha activity during the first three years of life, although weaker and slower maturing compared to sighted subjects. The first great differentiation between blind and sighted subjects occurs between 3 and 6 years of age. Starting in this period, reduced alpha activity increases the probability of motor impairment in blind subjects, likely because of impaired perception/interaction. These results show that visual experience mediates the neural mechanisms generating alpha oscillations during the first years of life, suggesting that it is a sensitive period for the plasticity of this process.